How do Lending Relationship Affect to Credit Accessibility in Cattle Farm in Indonesia? - Asnawi, Aslina; Nurani Sirajuddin, Sitti; Sri Lestari, Veronica (European Journal of Sustainable Development, 2014)
Financing aspect is one of the barriers still faced by the majority of beef cattle farmers in Indonesia. Today quite a lot of financing for both beef cattle breeding business sourced from banks or aid from the government. However, the accessibility level of funding is still relatively low. This study examines how the lending relationship between the farmers and the lenders affect to the funding accessibility for farmers. The intensity and duration of visits relationship between borrowers and lenders are the indicator of the level of relationship. The more closely the relationship will be higher levels of accessibility that demonstrated by the existence of credit support ever obtained by the breeders. Key words: access to credit, cattle farm, lending relationship